Binary Zn–Ti alloys for orthopedic applications: Corrosion and degradation behaviors, friction and wear performance, and cytotoxicity. (30th May 2021) - Wang, Kun; Tong, Xian; Lin, Jixing; Wei, Aiping; Li, Yuncang; Dargusch, Matthew; Wen, Cuie
Abstract: Zinc (Zn) and its biocompatible and biodegradable alloys have substantial potential for use in orthopedic implants. Nevertheless, pure Zn with a hexagonal close-packed crystal structure has only two independent slip systems, therefore exhibiting extremely low elongation and yield strength in its as-cast condition, which restricts its clinical applications. In this study, as-cast Zn–xTi (titanium) (x = 0.05, 0.10, 0.20, and 0.30 wt.%) binary alloys were hot-rolled and their microstructures, mechanical properties, wear resistance, and cytocompatibility were comprehensively investigated for orthopedic implant applications. The microstructures of both as-cast and hot-rolled Zn–xTi alloys consisted of an α-Zn matrix phase and a TiZn16 phase, while Zn–0.2Ti and Zn–0.3Ti exhibited a finer α-Zn phase due to the grain-refining effect of Ti. The hot-rolled Zn–0.2Ti alloy exhibited the highest yield strength (144.5 MPa), ultimate strength (218.7 MPa), and elongation (54.2%) among all the Zn–xTi alloys. The corrosion resistance of Zn–xTi alloys in Hanks' solution decreased with increasing addition of Ti, and the hot-rolled Zn–0.3Ti alloy exhibited the highest corrosion rates of 432 μm/y as measured by electrochemical testing and 57.9 μm/y as measured by immersion testing. The as-cast Zn–xTi alloys showed lower wear losses than their hot-rolled counterparts. The extracts of hot-rolled Zn–xTi alloys at concentrations of ≤ 25% showed no cytotoxicity to MG-63 osteosarcoma cells and the extracts of Zn–xTi alloys exhibited enhanced cytocompatibility with increasing Ti content.